Better Students Ask More Questions.
Simplify the following expressions and solve the equations.
1 Answer | add yours
I will only do first part as it is instructed to avoid any multiple questions.
` 1/(x-2)+(2x)/((x-2)(x-8)) = x/(2(x-8))`
`(x-8)/((x-2)(x-8))+(2x)/((x-2)(x-8)) = x/(2(x-8))`
`(x-8)+2x = (x(x-2))/2`
`2x-16+4x = x^2-2x`
`x^2-8x+16 = 0`
`(x-4)^2 = 0`
`x = 4`
So the answer is x = 4
Posted by jeew-m on July 24, 2013 at 6:32 PM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.